Acute Diffuse Renal Tubulopathy in a Patient With Lung Cancer: A Case Report - Tseng, Po-Jung; Yan, Ming-Tso (Frontiers in Medicine, 2021)
Immune checkpoints inhibitors (ICPIs) as either a frontline or adjuvant therapy showed favorable outcome among diverse malignancies. The immune related adverse events (IRAEs) are increasingly encountered but the kidneys are rarely affected. A 67-year-old man with stage IV squamous cell carcinoma of the lung presented with acute kidney injury and hypercalcemia secondary to bone metastasis. After the aggressive saline infusion and denosumab 60 mg administration, his renal function and serum calcium level were recovered on day 4. For his intolerance with chemotherapy, immunotherapy with monoclonal antibody targeting programmed cell death protein-1 (PD-1), pembrolizumab 2mg/kg, was used on day 4. On day 11, polyuria, non-albumin dominant proteinuria and severe deficiencies of electrolytes (potassium 2.5 mmol/L, calcium 5.5 mg/dL, magnesium 1.3 mg/dL and phosphate 1.5 mg/dL) with concomitant renal wasting were developed acutely. Except for postponing next pembrolizumab, prednisolone 1 mg/kg/day was used on day 13. On day 27, his polyuria subsided and urine protein loss resolved. Otherwise, his serum levels of potassium, phosphate, calcium and magnesium all returned within reference range. This case highlighted that renal IRAEs, albeit uncommon, could be severe and potentially life threatening if left unrecognized and untreated. Early recognition of renal IRAEs and prompt withdrawal of culprit ICPIs may help to achieve less morbidity.